"Emplaced" tradition - Hrobat Virloget, Katja (Traditiones (Ljubljana), 2012)
Since the expulsion of "folk" from the academic discourse the research of folk traditions seems inappropriate for a modern ethnologist. However, the landscapes are endowed with collective memory and meaning, given by the tradition. In the "emplaced" tradition can be discerned some continuity by which continuity includes change. Moreover, the aim of the paper is to show new dimensions of research and meanings, if the tradition is researched from the space-place perspective.
Keywords: ethnology; etnologija; ljudsko izročilo; ljudska kultura; karst; Kras